A nyelvi produktivitás jelentősége - Károly Sándor (Acta Universitatis Szegediensis : sectio ethnographica et linguistica = néprajz és nyelvtudomány = étnografiâ i azykoznanie = Volkskunde und Sprachwissenschaft, 1979)
This paper contains the following issues: 1. Productivity is a substantial property of the language. 2. Productivity in the works of Paul and Saussure. 3. Productivity of linguistic units and rules. 4. Productivity and word semantics. 5. The weak rule and the rule with a closed list. The role of productivity in the delimitation of centre and periphery of language. 6. Productivity, production, generation.